User-Centered Design of Trauma Systems Solutions for Retriage of Patients With Injury: Mixed Methods Study - Slocum, John Dwight; Jelke, David; Mai, Qixuan; Johnson, Julie K; Nguyen, My L T; Cong, Lixuan; Chandrasekaran, Adithya; Holl, Jane L; Moklyak, Yuriy; Mis, Justin; Gabaldo, Molly; Adams, James G; et al. (Journal of medical Internet research, 2025)
Retriage is the emergent interhospital transfer of severely injured patients from nontrauma and low-level trauma centers to high-level trauma centers. An estimated 17%-34% of patients with traumatic injury are undertriaged to nontrauma or low-level trauma centers in the United States each year. These patients see 30% increased odds of mortality at 48 hours and nearly 4-fold increased odds of overall mortality. However, 30%-50% of undertriaged patients are never retriaged to a high-level trauma center. Informatics-driven solutions facilitate time-sensitive exchange of patient information in other health care contexts. Few studies have explored how informatics-driven solutions can be tailored to address obstacles to timely, effective retriage. We applied user-centered design to develop a robust, acceptable, and feasible digital health solution to improve the retriage process. This was a mixed methods, observational, cross-sectional study. Potential frontline users of an intervention and hospital leadership were recruited to participate. Individuals in these roles included trauma medical directors, emergency department directors, trauma surgeons, emergency medicine physicians, emergency department nurse managers, emergency department nurses, trauma coordinators, emergency department bed managers, and health unit coordinators at nontrauma or low-level trauma centers and high-level trauma centers. We applied the 5-phase user-centered design approach, including phase 1: understanding the design needs, through site visit observations and focus groups; phase 2: ideation of potential solutions through a second round of virtual focus groups; phase 3: rank ordering solutions to identify the most robust, acceptable, and potentially feasible solutions; phase 4: prototyping by creating low-fidelity prototypes for the highest-ranked solutions; and phase 5: validation of the robustness of the prototypes through virtual focus groups. Validation approaches included asking frontline end users to assess the feasibility of each prototype and whether prototypes would address the identified retriage failures and barriers. In addition, leaders were asked to assess the feasibility of implementing the proposed solutions in their trauma center. All virtual sessions were recorded, transcribed, and inductively coded to generate themes of robustness, acceptability, and feasibility of the retriage solution. Thematic analysis was anchored on the desirability, viability, and feasibility design thinking methodology. Nineteen sessions were conducted across all 5 phases with 49 participants from 12 trauma centers across Illinois. Participants included frontline users and leadership. The key design requirement was resource transparency between centers. The ideation phase produced 70 solutions. A systemwide bed tracker was ranked the highest by participants. Prototyping and validation resulted in a centralized, systemwide, bed tracker with hourly updated bed availability being the final solution to improve the retriage of patients with traumatic injury from non- or low-level trauma centers and high-level trauma centers. A 5-phase user-centered design approach resulted in a single solution consisting of a digital bed-tracker with frequently updated data on beds at high-level trauma centers to improve retriage.